The Use of Japanese Adverb [ikura] - Dinda Gayatri Ranadireksa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Japanese language has so much uniqueness in its characters, especially when it comes to similar words. One of those words is [ikura] as known as a question word to express ‘how much” or “no matter how much” in English. The word is used to be written as 幾ら (ikura) but nowadays it is not necessary to write it in Kanji (Chinese character), but just written by Hiragana.For Japanese learners, it is sometimes confusing how to divide the meaning and the use of [ikura] comparing to other word like [donna ni] when it is followed by auxiliary -temo. Both are remarkably similar but surely have different meanings. This research is to study the use and the meaning of Japanese [ikura], and thus compared to [donna ni]. By conducting the observation on those meanings, we will know the differences between the two words so that Japanese learners will be able to know the correct use of these expressions.